The Hypothiocyanite and Amantadine Combination Treatment Prevents Lethal Influenza A Virus Infection in Mice - Ashtiwi, Nuha Milad; Sarr, Demba; Nagy, Tamás; Reneer, Z. Beau; Tripp, Ralph A.; Rada, Balázs (Frontiers in Immunology, 2022)
Influenza virus has a large clinical burden and is associated with significant mortality and morbidity. Development of effective drugs for the treatment or prevention of influenza is important in order to reduce its impact. Adamantanes and neuraminidase inhibitors are two classes of anti-influenza drugs in which resistance has developed, thus there is an urgent need to explore new therapeutic options. Boosting antiviral innate immune mechanisms in the airways represents an attractive approach. Hypothiocyanite (OSCN-) is produced by the airway epithelium and is effective in reducing replication of several influenza A virus strains in vitro. It remains, however, largely unexplored whether OSCN- has such an antiviral effect in vivo. Here we determined the therapeutic potential of OSCN-, alone or in combination with amantadine (AMT), in preventing lethal influenza A virus replication in mice and in vitro. Mice intranasally infected with a lethal dose of A/Puerto Rico/8/1934 (H1N1) or A/Hong Kong/8/1968 (H3N2) were rescued by the combination treatment with OSCN- and AMT. Monotherapy with OSCN- or AMT alone did not substantially improve survival outcomes. However, AMT + OSCN- treatment significantly inhibited viral replication and in vitro treatment inhibited viral entry and nuclear transport of different influenza A virus strains (H1N1, H3N2) including the AMT-resistant strain A/WSN/33 (H1N1). A triple combination treatment consisting of AMT, oseltamivir and OSCN- was also tested and further inhibited in vitro viral replication of the AMT-resistant A/WSN/33 strain. These results suggest that OSCN- is a promising anti-influenza treatment option when combined with other antiviral drugs.